2020
DOI: 10.1007/s10100-020-00706-5
|View full text |Cite
|
Sign up to set email alerts
|

IP solutions for international kidney exchange programmes

Abstract: In kidney exchange programmes patients with end-stage renal failure may exchange their willing, but incompatible living donors among each other. National kidney exchange programmes are in operation in ten European countries, and some of them have already conducted international exchanges through regulated collaborations. The exchanges are selected by conducting regular matching runs (typically every three months) according to well-defined constraints and optimisation criteria, which may differ across countries… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…The Czech Republic and Austria share their full registry data and allow algorithms to find solutions across registries. In Spain-Italy-Portugal collaboration, countries find their internal matches first and share the remaining data with other countries [14]. US also started multi-hospital exchange programs in 2008 [27].…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…The Czech Republic and Austria share their full registry data and allow algorithms to find solutions across registries. In Spain-Italy-Portugal collaboration, countries find their internal matches first and share the remaining data with other countries [14]. US also started multi-hospital exchange programs in 2008 [27].…”
Section: Introductionmentioning
confidence: 94%
“…There are multiple challenges in multi-registry/international exchange programs (mKEP) like data among registries, different bounds on cycle lengths, and simultaneous or non-simultaneous execution of transplants [14]. It has been shown that there could be cases where individual registries have incentives not to share full data to mKEP, which restrict registries from forming a coalition naturally.…”
Section: Introductionmentioning
confidence: 99%
“…One of the main applications of operations research was healthcare, e.g. [21,12,30,24,4,18]. However, most of the papers in the operations research field are concerned with either simulation frameworks [27,23,16] or resource allocation problems [22,17,13,3].…”
Section: Related Workmentioning
confidence: 99%
“…70 The combined pool between the three countries included 113 pairs and resulted in one 3-way cycle https://www.lamoncloa.gob .es/lang/en/gobierno/news/Paginas/2018/20180808transplant.aspx. 71 See Biró et al (2019c) and Mincu et al (2020) for more forms of collaborations in European countries. 72 Of course, some transactions may have negative externalities that directly harm third parties, and it is easy to understand the objections of those who are harmed.…”
Section: Endnotesmentioning
confidence: 99%